Sekularisme, Epistemologi Reformed, dan Liturgi: Menimbang Peran Liturgi dalam Konteks Masyarakat Sekuler - Samuel Vincenzo Jonathan; Albertus Harsawibawa (Societas Dei: Jurnal Agama dan Masyarakat, 2022)
Secularism is a condition of the times when we live in today. It gives awareness to the global community that in reality there is only the immanent—there is no God. So, theism is seen as just one of the many available options: atheism becomes even more attractive to embrace. Generally, a theist will respond by demonstrating the theism plausibility  through positive arguments  about the existence of God. The author rejects this and offers an approach from Reformed epistemology on the problem, as it is a thesis on how one knows God. Through Reformed epistemology, the author views secularism as what he considers   as a cognitive environment. A cognitive environment  prevents the “knowing subject” from knowing God, as the authors point out that the appropriate response to secularism is  involving the “knowing subject” into the liturgy. Thus, liturgy can also be understood as an act that has an epistemic dimension  which enables a person  knowing God.